HLA-DQ Genotype Is Associated with Accelerated Small Bowel Transit in Patients with Diarrhea-Predominant Irritable Bowel Syndrome - Vazquez-Roque, Maria I. (2011)
BACKGROUND: Colonic transit (CT) is accelerated in 46% of patients with diarrhea-predominant irritable bowel syndrome (IBS-D). Improvement in IBS-D with gluten withdrawal is associated with HLA-DQ2 positivity; the mechanism of improvement is unclear. OBJECTIVE: To determine if HLA-DQ2 or HLA-DQ8 positive IBS-D patients have faster small bowel (SB) or CT than HLA-DQ2 and HLA-DQ8 negative patients. METHODS: Among 94 IBS-D patients who previously provided DNA samples, 64 had undergone validated measurements of CT (geometric center at 24h [GC24]); 50 of the patients also had measurement of gastric emptying (GE) and 54 of SB transit (colonic filling at 6h [CF6h]). HLA-DQ status was determined by tag SNP approach. Associations of CF6h and GC24 with HLA-DQ2 and HLA-DQ8 status were assessed using analysis of covariance (ANCOVA), adjusting for BMI. RESULTS: Mean age was 40.8±1.6y; 98.5% were female. In 60/64 patients, celiac disease was excluded by serology or histology. There were no significant differences in age or BMI among the different HLA-DQ groups. Independently, patients positive for HLA-DQ2 had numerically greater CF6h compared to HLA-DQ2 negative (p=0.065), and those positive for HLA-DQ8 had greater CF6h compared to HLA-DQ8 negative patients (p=0.021). GE was not associated with HLA-DQ2 and HLA-DQ8 status. Patients positive for both HLA-DQ2 and HLA-DQ8 had greater CF6 (p=0.013) and numerically higher, but not significant, GC24 (p=0.38) compared to HLA-DQ2 and HLA-DQ8 negative patients. CONCLUSION: IBS-D patients positive for HLA-DQ8 or for both HLA-DQ2 and HLA-DQ8 have faster SB transit. The mechanism of the accelerated SB transit and the effect of gluten withdrawal on SB function in IBS-D deserve further investigation.